Urban water-energy-food-climate nexus in integrated wastewater and reuse systems: Cyber-physical framework and innovations. (15th September 2021) - Radini, Serena; Marinelli, Enrico; Akyol, Çağrı; Eusebi, Anna Laura; Vasilaki, Vasileia; Mancini, Adriano; Frontoni, Emanuele; Bischetti, Gian Battista; Gandolfi, Claudio; Katsou, Evina; Fatone, Francesco
Graphical abstract: Highlights: WEFC nexus in urban/peri-urban reuse systems can support energy transition policy. Models and tools demonstrate decision support systems based on multi-sources data. A comprehensive tool that considers all the sectors of the WEFC nexus is still missing. Digital solutions can reduce the fragmentation of knowledge across the water value chain. Abstract: Wastewater treatment is one of the major carriers of the water-energy-food-climate (WEFC) nexus, and although the relationship between water and energy is well recognized, there is still a lack of adequate analysis of the cyber-physical framework to address and assess urban and peri-urban WEFC nexus in an integrated approach. In this review paper, we deeply analyze and summarize the modelling tools and data that are currently used to quantify the nexus in wastewater treatment. Currently, comprehensive models and tools are missing that consider the interconnections amongst catchment, sewer network, wastewater treatment plant (WWTP), river and climatic system in a holistic approach and define relevant monitoring requirements and trustable information provision. Cyber-physical systems provide a technological ground for an efficient management of such integrated systems. The nexus approach in precision irrigation and smart agriculture is further discussed in the paper, highlighting the issue of water reuse and the engagement of different levels of stakeholders. Digital solutions and serious games addressing the nexus in urban and peri-urban water management are also presented to facilitate innovative practice aspects and to foster public involvement. Adaptable digital solutions can help to understand stakeholders' perception of water quality and its governance and to improve levels of awareness and collaboration between utilities, authorities, farmers and citizens. Finally, recommendations on the added value of currently used models, tools and possible digital solutions are given to WWTP and reclamation managers and/or operators to bring the WEFC nexus approach on the operative environment.